Teaching a Preschooler with ASD to Cooperate in Relinquish Reinforcers and Transition to Learning Activities During Skill-Based Treatment (SBT) - L.L. Beznosikova; L.A. Ostrovskaya (Moscow State University of Psychology and Education, 2021)
A child, 5 years and 3 months old with autism spectrum disorder (ASD) and severe problem behavior was taught to stop playing and move to the learning activities. The study demonstrates the result of 2 phases of skill-based treatment (SBT) developed by Dr. Gregory Hanley: a) relinquish reinforcement phase (CAB 1) and b) transition phase (CAB 2). This is an individual case analysis, the study was conducted in a multiple baseline design across behaviors, lasted 8 weeks, and included the measurements of problem behaviors and learned skills during each training trial. As a result of 15-hour training, the child was taught the skill of stopping the play and transition to the learning area. Learners' responses as willingness to listen to a teacher and ready to learn have emerged. At the same time, dangerous problem behavior was reduced to zero during the transition from a preferred activity to a learning area while being instructed. Transition responses were spontaneously generalized with people who were not present in the classroom (parents, tutors) and transferred to the new conditions (home and pre-school).